Desenvolvimento de cinco porta-enxertos cítricos e do enxerto variedade folha murcha em ambientes com diferentes níveis de sombreamento - Martins, Madles Queiroz (2011)
The variation in light intensity on plants species can lead to different responses in their physiological, biochemical, anatomical and growth. The objective of this study was to evaluate the influence of environments with different levels of shading in th